Chypre à l'épreuve de la domination lagide Testimonia épigraphiques sur la société et les institutions chypriotes à l'époque hellénistique - Michel, Anaïs (Bibliothèque des Écoles françaises d'Athènes et de Rome (BEFAR), 2020)
Cypriot inscriptions provide a first-hand testimony of the evolution of the Ptolemaic dynasty during the three centuries of its existence and activity in Cyprus. They also reveal the changes and continuities of a society in the process of being redefined. This research leads to new conclusions in three major domains: politics and administration, religious and cultural practices, royal ideology and interactions between the Cypriot society and the Ptolemies. This volume thoroughly explores the conditions under which the Ptolemaic dynasty established its administration into Cypriot political, social and religious structure, traditionally marked by the coexistence of kings and cities. The study further shows, following the most recent works on the Greek cities' political and institutional life during the Hellenistic period, that the negotiation between the Cypriot cities and the Ptolemies proceeds from an original interpretation of the dialogue between the poleis and the kings. Anaïs Michel is a member of the French School at Athens. She is a specialist in Greek epigraphy, and completed her PhD in Greek archaeology. Her research focuses on the relationship between the Ptolemies and the Cypriot society, royal Ptolemaic cult and Ptolemaic administration outside Egypt. She is the author of several articles on Hellenistic Cyprus and contributes to the Bulletin épigraphique of the Revue des études grecques. She also carries research on the inscriptions of the island of Delos where she conducts the study of the decrees of the Hellenistic period.